2014
DOI: 10.1108/jkm-09-2013-0341
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of knowledge sharing on the relationship between trust and virtual team effectiveness

Abstract: Purpose – The limited proximal communication between virtual team members can create a lack of trust among members which can significantly reduce the effectiveness of these teams. Hence, this study was conducted to examine the relationship between trust and virtual team effectiveness by looking into the mediating effect of knowledge sharing. Design/methodology/approach – This is a cross-sectional study conducted in a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 35 publications
8
99
0
Order By: Relevance
“…Pangil & Chan (2014) in their study concluded that knowledge sharing is important regardless the team type, as organizations have made increased use of work teams as fundamental units of organizational structure reliant on leadership. According to Moriarty project or service".…”
Section: Knowledge Sharing and Team Effectivenessmentioning
confidence: 99%
“…Pangil & Chan (2014) in their study concluded that knowledge sharing is important regardless the team type, as organizations have made increased use of work teams as fundamental units of organizational structure reliant on leadership. According to Moriarty project or service".…”
Section: Knowledge Sharing and Team Effectivenessmentioning
confidence: 99%
“…Consequently, this investigation was directed to inspect the connection amongst trust and virtual group viability by investigating the interceding impact of information sharing (Pangil & Moi Chan, 2014), Trust has been established to be a huge indicator of virtual group adequacy. Be that as it may, this paper demonstrates the impact of various sorts of trust and the part of learning to partake in intervening the connection amongst trust and virtual group viability.…”
Section: Building Trust and Organizational Commitment In Virtual Teamsmentioning
confidence: 99%
“…As previously discussed, virtual teams need trust among members in order to achieve their goals, since trust affects team's efficiency (Pangil and Chan, 2014). Trust models can be used to monitor trust among team members.…”
Section: The Frameworkmentioning
confidence: 99%
“…Thus, trust reduces the risk and cost of monitoring (Striukova and Rayna, 2008). It also impacts in information sharing (Pangil and Chan, 2014), cohesion (Kuo and Yu, 2009) and cooperation (Striukova and Rayna, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation